13. Solve for m. Assume that none of the denominatons are equal to 0
Plz help me
![13 Solve for m Assume that none of the denominatons are equal to 0Plz help me class=](https://us-static.z-dn.net/files/d66/4b8660f695f3564022084378e7f8103c.jpg)
Answer:
m = (ps - b - uxs/t) / ux/t - p
Step-by-step explanation:
ux/t +b/m+s =p
multiplying throughout by (m+s) we get:
ux/t(m+s) + b = p(m+s)
open the brackets:
uxm/t + uxs/t + b = pm + ps
bring on one side of the equal sign all terms containg m, to make it the subject:
m(ux/t - p) = ps - b - uxs/t
m= (ps - b - uxs/t) / ux/t - p